Reading and young children with Jan McCarthy (Washington : The association, 1985)
Carolyn S. Dorell directora of Earth Childhood entrevista al señor Jan McCarthy, profesor de Indiana State University sobre "La lectura y los niños".
Keywords: EDUCACION PREESCOLAR; EDUCACION; LECTURA; VIDEOGRABACIONES